Effect of Metformin on Anthropometric Measurements and Hormonal and Biochemical Profile in Patients with Prediabetes - Mustafa Safiah; Dana Hyassat; Yousef Khader; Oraib Farahid; Anwar Batieha; Mohammed El-Khateeb; Kamel Ajlouni (Journal of Diabetes Research)
Objectives. Metformin is the most widely preferred first-line oral antidiabetic agent that results in clear benefits in blood sugar regulation and diabetes-related complications. This study is aimed at assessing the effect of metformin on anthropometric, hormonal, and biochemical parameters in patients with prediabetes or insulin resistance. Methods. A prepoststudy was conducted among 52 patients with prediabetes or insulin resistance who met the inclusion criteria. Weight, body mass index (BMI), and waist circumference were measured before and 12 months after metformin treatment. Serum concentrations of sex steroids, gonadotropins, and lipids were also assessed. Homeostasis model assessment (HOMA) index and quantitative sensitivity check (QUICKI) index scores were calculated before metformin treatment and after 12 months of use. Results. After 12 months of metformin treatment, female patients had significant reduction in weight, BMI, and waist circumference after adjusting for age. Metformin use for 12 months resulted in significant reduction in mean fasting blood glucose and HbA1c in females only. Total cholesterol decreased significantly among men only and serum HDL-C showed a significant rise among females only. Serum LDL-C and triglycerides did not change significantly in females and males. Our study did now significant changes in ACTH and cortisol levels in both females and males after metformin treatment. Metformin use resulted in significant increase in luteinizing hormone (LH) and progesterone levels in males, while it was associated with significant increase in prolactin, follicular stimulating hormone (FSH), and dehydroepiandrostenedione-sulphate (DHEA-S) levels and significant decrease in total testosterone level in females. Conclusion. Metformin treatment in females with prediabetes reduces BMI, waist circumference, fasting blood glucose, and HbA1c. The changes in the studied parameters differed significantly according to sex.